(untitled) (European Journal of Marketing and Economics, 2019)
Global developments have seen the rapid growth of international marketing due to trade liberalization and a reduction in barriers to global trade. This has resulted in opening up of new markets and availability of foreign products in domestic markets. China has taken a leading role in global trade due to its low levels of production costs and technological advancements. Chinese electronic products can now be found most parts of the world. This study attempted at determining the attitudes of consumers towards made in China products. It was guided by the concepts of consumer ethnocentrism and consumer animosity and how these influenced the willingness to buy Chinese electronic products. A sample size of 385 was chosen with 319 participating. Data was collected through a questionnaire adopted and modified from a study by Quang, DinhChien and Long (2017) in Vietnam. Factor analysis, confirmatory factor analysis (CFA) and structural equation modelling (SEM) techniques were used in the analysis. From the findings, it was evident that amongst the Kenyans, consumer ethnocentrism influences the level of consumer animosity. In instances where consumer animosity existed, it did not have an impact on product judgments. Though the respondents had expressed some level of animosity towards China, the same did not have a negative impact on product judgments. In terms of consumer ethnocentrism, the respondents indicated that it had a negative impact on product judgments, an indication that a high level of ethnocentrism will lead to unfavourable attitudes towards a product from a foreign country.